Multiple factors modulate biofilm formation by the anaerobic pathogen Clostridium difficile - Dapa, Tanja; Leuzzi, Rosanna; Ng, Yen K.; Baban, Soza T.; Adamo, Roberto; Kuehne, Sarah A.; Scarselli, Maria; Minton, Nigel P.; Serruto, David; Unnikrishnan, Meera (2013)
Bacteria within biofilms are protected from multiple stresses, including immune responses and antimicrobial agents. The biofilm-forming ability of bacterial pathogens has been associated with increased antibiotic resistance and chronic recurrent infections. Although biofilms have been well studied for several gut pathogens, little is known about biofilm formation by anaerobic gut species. The obligate anaerobe Clostridium difficile causes C. difficile infection (CDI), a major health care-associated problem primarily due to the high incidence of recurring infections. C. difficile colonizes the gut when the normal intestinal microflora is disrupted by antimicrobial agents; however, the factors or processes involved in gut colonization during infection remain unclear. We demonstrate that clinical C. difficile strains, i.e., strain 630 and the hypervirulent strain R20291, form structured biofilms in vitro, with R20291 accumulating substantially more biofilm. Microscopic and biochemical analyses show multiple layers of bacteria encased in a biofilm matrix containing proteins, DNA, and polysaccharide. Employing isogenic mutants, we show that virulence-associated proteins, Cwp84, flagella, and a putative quorum-sensing regulator, LuxS, are all required for maximal biofilm formation by C. difficile. Interestingly, a mutant in Spo0A, a transcription factor that controls spore formation, was defective for biofilm formation, indicating a possible link between sporulation and biofilm formation. Furthermore, we demonstrate that bacteria in clostridial biofilms are more resistant to high concentrations of vancomycin, a drug commonly used for treatment of CDI. Our data suggest that biofilm formation by C. difficile is a complex multifactorial process and may be a crucial mechanism for clostridial persistence in the host.